Evaluation of multisystemic therapy pilot services in Services for Teens Engaging in Problem Sexual Behaviour (STEPS-B): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Fonagy, Peter; Butler, Stephen; Baruch, Geoffrey; Byford, Sarah; Seto, Michael; Wason, James; Wells, Charles; Greisbach, Jessie; Ellison, Rachel; Simes, Elizabeth
Abstract Background Clinically effective and cost-effective methods for managing problematic sexual behaviour in adolescents are urgently needed. Adolescents who show problematic sexual behaviour have a range of negative psychosocial outcomes, and they and their parents can experience stigma, hostility and rejection from their community. Multisystemic therapy (MST) shows some evidence for helping to reduce adolescent sexual reoffending and is one of the few promising interventions available to young people who show problematic sexual behaviour. This paper describes the protocol for Services for Teens Engaging in Problem Sexual Behaviour (STEPS-B), a feasibility trial of MST for problem sexual behaviour (MST-PSB) in antisocial adolescents at high risk of out-of-home placement due to problematic sexual behaviour. Methods/Design Eighty participants and their families recruited from five London boroughs will be randomized to MST-PSB or management as usual with follow-up to 20 months post-randomization. The primary outcome is out-of-home placement at 20 months. Secondary outcomes include sexual and non-sexual offending rates and antisocial behaviours, participant well-being, educational outcomes and total service and criminal justice sector costs. Feasibility outcomes include mapping the clinical service pathways needed to recruit adolescents displaying problematic sexual behaviour, acceptability of a randomized controlled trial to the key systems involved in managing these adolescents, and acceptability of the research protocol to young people and their families. Data will be gathered from police computer records, the National Pupil Database and interviews and self-report measures administered to adolescents and parents and will be analysed on an intention-to-treat basis. Discussion The STEPS-B feasibility trial aims to inform policymakers, commissioners of services and professionals about the potential for implementing MST-PSB as an intervention for adolescents showing problem sexual behaviour. Should MST-PSB show potential, STEPS-B will determine what would be necessary to implement the programme more fully and at a scale that would warrant a full trial. Trial registration ISRCTN28441235 (registered 25 January 2012).